A succession of quartz veins in Archean metaturbidites, Yellowknife Bay, Slave Province - Fyson, W. K. (Canadian Journal of Earth Sciences, 1987)
The style of extensional quartz veins changed during deformation and metamorphism of greywacke–mudstones near Yellowknife, with successive types of veins accompanying a progression from steeply plunging, predominantly macroscopic F 1 , and F 2 folds to mesoscopic F 3 folds and subvertical S 3 axial planar cleavages. (A) Early-stage multiple bedding-parallel veins are confined to pelitic units. Some form saddle reefs around hinges of F 1 and a few later folds, whereas others are unrelated to fold hinges. Emplacement of most bedding veins during or before F 1 folding is suggested. (B) Echelon veins pre-dominantly lie stratabound within pelites. Folding about S 3 cleavage indicates a pre-F 3 or early F 3 origin. (C) Foliation veins more commonly cross sandstones than pelites and follow S 3 or F 3 axial surfaces. Boudinage of the veins indicates emplacement before S 3 was fully developed. (D) Sporadic veins, discordant to bedding and cleavage, vary from undeformed to folded about S 3 . Evidently these veins were emplaced towards the end or after F 3 folding.The change from pelite as the preferred host rock for bedding and echelon veins to sandstone for foliation veins could reflect migration of loci of hydraulic fracturing as fluid was produced and lost during metamorphism. Bedding and foliation veins apparently followed weakness planes (bedding fissility and cleavage), whereas the echelon vein arrangement suggests that during an intermediate stage of deformation pelites acted as shear zones. All veins could have formed during variably directed, subhorizontal, tectonic compression.